The Effect of Self-Determination and Self-Efficacy on Students' Career Maturity Through Family Social Support - Nurul Kholifatun; Ali Formen; Sugiyo (Study Program of Guidance and Counselling, Post Graduate Program, Universitas Negeri Semarang, 2024)
The expansive number of unemployed high school graduates is purportedly due to the need to develop career arranging by understudies after graduating from school. With respect to this issue, the show investigated and analyzed the impact of self-determination and self-efficacy on career development through family social back at vocational high schools majoring in hospitality department or SMK Perhotelan in Semarang City. The research method used was quantitative with an ex post facto approach. In collecting the information, a few scales were utilized, such as a mental scale of self-determination, self-efficacy, family social back, and career development. Based on the discoveries, self-determination contributed a positive and critical impact on students' family social back, self-efficacy had a positive and noteworthy impact on students' family social bolster, self-determination had a positive and critical impact on students' career development, self-efficacy had a positive and critical impact on student's career development, and family social bolster had a positive and critical impact on students' career development. Other discoveries were there found a circuitous impact of self-determination on the career development of SMK Perhotelan understudies in Semarang City through family social support, and there was an indirect effect of self-efficacy on the career maturity of SMK Perhotelan students in Semarang City through family social support. It can be concluded the a need to improve students’ career maturity through guidance and counseling services.